Acute and Rapid Development of Spontaneous Spinal Epidural Hematoma Associated with Combined Aspirin-Dipyridamole Therapy: A Case Report. Issue 1 (January 2017) - Yamaguchi, Kent; Mathew, Justin; Lhi, James M.; Park, Don Young
Abstract : Case: Spontaneous spinal epidural hematoma (SSEH) is a known, although rare, clinical entity that may be challenging to diagnose. This case report describes the rapid development of a large SSEH in an elderly patient on aspirin-dipyridamole combination therapy after she shifted her position in bed. Magnetic resonance imaging obtained 4 hours after the onset of symptoms demonstrated a large spinal epidural hematoma that extended from T4 to L1. Conclusion: With early diagnosis, the patient was successfully treated with a laminectomy and evacuation of the hematoma, and there was full neurological recovery.